Pengaruh Lingkungan Kerja Fisik dan Komunikasi Internal terhadap Kepuasan Kerja Pegawai Dinas Pendidikan Kota Cimahi - La Nuhu, Ardhalina; Mochamad Vrans Romi (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the influence of the physical work environment and internal communication on employee job satisfaction at the Cimahi City Education Office. The research method used a quantitative approach with field research and literature techniques, where data were collected through interviews, questionnaires, and documentation. The research sample consisted of 46 randomly selected respondents, and data processing was carried out using multiple linear regression analysis with the help of SPSS version 26.0. The results showed that partially, the physical work environment had a positive and significant effect on employee job satisfaction with a significance value of 0.009 <0.05, and internal communication also had a significant positive effect on job satisfaction with a significance value of 0.000 <0.05. Simultaneously, both variables had a significant effect on employee job satisfaction with a calculated F_value of 27.413, greater than the F_table of 3.067 and an R Square of 0.560, which means the contribution of both variables to employee job satisfaction was 56%. The conclusion of this study is that the better the physical work environment and the more effective internal communication, the higher the level of employee job satisfaction at the Cimahi City Education Office.   Keywords: Physical Work Environment, Internal Communication, Job Satisfaction, Employees